The relationship of total body composition with bone mineral density in postmenopausal women with type 2 diabetes - Vadim Valer'evich Klimontov; Olga Nikolaevna Fazullina (Сахарный диабет)
Aim. To determine the relationship between bone mineral density (BMD) and total body composition in postmenopausal women with type 2 diabetes. Materials and Methods. The study included 78 women, from 50 to 70 years of age (median 63 years). Twenty women had normal body mass index (BMI), 29 ones were overweight and 29 had obesity. The body composition and BMD was studied by dual-energy X-ray absorptiometry. Results. Women with normal BMD had higher BMI, total and truncal fat mass, as well lean mass as compared to women with osteoporosis and osteopenia (all p